2009
DOI: 10.1111/j.1439-0272.2009.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme activity and MDA level in the rat testis following chronic administration of ghrelin

Abstract: Ghrelin has recently been reported to exert beneficial effects on various oxidative stresses as a result of its antioxidant properties. Therefore, we designed this study to explore the probable antioxidative effects of this peptide in the testis. Twenty-eight male adult Wistar rats were divided into equal control and treatment groups. In the treatment group, 1 nmol of ghrelin was administered as subcutaneous injection for 10 consecutive days or vehicle (physiological saline) to the control rats. The control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 33 publications
4
38
0
2
Order By: Relevance
“…This was attributed to the decreased bioactivation of PCM caused by the ghrelin pretreatment. This result was supported by previous studies showing that ghrelin induced reduction of the increased level of MDA in preadipocyte cell culture (Zwirska-Korczala et al, 2007) testis and ovary of rats (Kheradmand et al, 2009;Kheradmand et al, 2010). Also, our study in agreement with Obay et al (2008) who demonstrated that pretreatment of rats with different doses of ghrelin prevented pentylenetetrazole-induced elevation in lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was attributed to the decreased bioactivation of PCM caused by the ghrelin pretreatment. This result was supported by previous studies showing that ghrelin induced reduction of the increased level of MDA in preadipocyte cell culture (Zwirska-Korczala et al, 2007) testis and ovary of rats (Kheradmand et al, 2009;Kheradmand et al, 2010). Also, our study in agreement with Obay et al (2008) who demonstrated that pretreatment of rats with different doses of ghrelin prevented pentylenetetrazole-induced elevation in lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
“…Ghrelin is secreted primarily from the stomach, but ghrelin transcripts have been found in many other organs, including the liver, kidney, lung, pancreas, hypothalamus and heart, suggesting an endocrine as well as extra-endocrine action of ghrelin (Kojima et al, 1999;Gnanapavan et al, 2002). Many studies have indicated that ghrelin has beneficial effects on gastrointestinal, cardiovascular, reproductive, immune and coagulation systems (Eter et al, 2007;Chang et al, 2004;Işeri et al, 2005;Kheradmand et al, 2009;Yada et al, 2006;Arıcı and Çetin, 2010). Other studies have revealed that ghrelin may be an antioxidant and anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…39 Kheradmand's studies showed that ghrelin has antioxidant properties in the rat testis and ovary tissues. 40,41 Moreover, one study proposed that ghrelin increases activity of SOD, CAT, GSH-Px in 3T3 L1 preadipocytes. 42 In our study activity of brain GPx, SOD and catalase were not influenced significantly by ghrelin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is the organic compound with the formula CH 2 (CHO) 2 and it is a bio-marker of oxidative stress in an organism and an increase of MDA level demonstrates oxidative stress [16] . Anti-oxidative activity of ghrelin has been reported in numerous studies [12,13,17] . Reports of Işeri et al [17] indicated anti-oxidative activity of ghrelin and its ameliorative ability for alendronate-induced oxidative stress, as MDA comes back to the control level after ghrelin infusion.…”
Section: Introductionmentioning
confidence: 99%
“…After identification of ghrelin in mammals by Kojima et al [2] so many relative studies were conducted on ghrelin properties. Studies conducted during last decade suggested various specifies and functions for ghrelin, such as GH-releasing [3] , osteogenesis [4,5] , hematopoiesis [6,7] , food intake and energy balance and regulation [8,9] , endocrine/ paracrine roles in pancreas [10,11] , and currently antioxidative effects [12,13] . Peptide structure of chicken ghrelin has 26 amino acids with 54% similarity to rat ghrelin [14] .…”
Section: Introductionmentioning
confidence: 99%